Rafflesia Indonesia Sebagai Motif Tekstil Printing Tas Fashion Wanita (Program Studi Pendidikan Seni Rupa FBS UNJ, 2021)
The purpose of the creation is to implement Rafflesia Indonesia as a motif with digital printing techniques in women's fashion bag products. This research method uses descriptive qualitative methods (literature study; research grants travel questions;). In the tour question grant effort, exploring the object that is used as a reference in making textile design motifs at Rafflesia Indonesia, then the digital printing process is carried out. The manufacture of women's fashion bags is carried out through digital and manual design exploration. This process needs to be done to produce product samples and determine the performance of task functions. The results obtained are 5 women's fashion bags that were created with the concept of multifunctional style; a blend of cow leather and polyester fabric according to the user's specifications; adjust color trends and fashion bags 2020. At the same time as an introduction and appreciation of Rafflesia Indonesia through the motifs displayed.